Molding of three-dimensional microcomponents - Hung, W. N. P.; Agnihotri, M. M.; Ali, Mohammad Yeakub; Yuan, S. (2006)
Traditional micromanufacturing has been developed for semiconductor industry. Selected micro electrical mechanical systems (MEMS) have been successfully developed and implemented in industry. Since current MEMS are designed for manufacture using microelectronics processes, they are limited to two-dimensional profiles and semiconductor based materials. Such shape and material constraints would exclude many applications that require biocompatibility, dynamic stress, and high ductility. New technologies are sought to fabricate three dimensional microcomponents using robust materials for demanding applications. To be cost effective, such microdevices must be economically mass producible. Molding is one of the promising replication techniques to mass produce components from polymers and polymer-based composites. This paper presents the development of a micromolding process to produce thermoplastic microcomponents. Mold design required precision fitting and was integrated with a vacuum pump to minimize air trap in mold cavities. Nickel and aluminum mold inserts were used for the study; their cavities were fabricated by combinations of available micromachining processes like laser micromachining, micromilling, micro electrical discharge machining, and focused ion beam sputtering. High and low density polyethylene, polystyrene polymers were used for this study. The effects of polymer molecular structures, molding temperature, time, and pressure on molding results were studied. Simulation of stress in the microcomponents, plastic flow in microchannels, and mold defects was performed and compare with experimental data. The research results showed that a microcomponent can be fabricated to the minimum size of 10 ± 1μm (0.0004 inch) with surface roughness <10 nm Rt. Molding of micro-size geartrains and orthopedic meso-size fasteners was completed to illustrate the capability of this process.